Pengaruh Pelatihan Kerja Terhadap Kinerja Pegawai Pada Lembaga Pemasyarakatan Kelas IIB Solok - Aulia Rakhman; Netty Indrawati; Selfidiana Roza (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to examine the effect of job training on employee performance at Class IIB Solok Penitentiary. While the research sample was determined using the saturated sample method by including all research samples in a population, for this research the sample was taken from all employees of Class IIB Solok Correctional Institution as many as 83 people. The types of data used include instrument testing, simple regression analysis, coefficient of determination and hypothesis testing. The results of this study indicate that there is a significant effect of job training on employee performance in all employees of Class IIB Solok Penitentiary. This is evidenced by using the t test with a tcount of 2.153 > ttable 1.664 with a significant value of 0.034 <0.05. It can be concluded that job training has an effect on employee performance in class IIB correctional institutions in Solok City or the hypothesis is accepted. This means that the job training provided is very influential for the performance of employees in class IIB correctional institutions in Solok City.